PETROLOGI DAN GEOKIMIA BATUAN GUNUNG API METULANGDI DAERAH LONGBIA, KALIMANTANTIMUR: IMPLIKASI TEKTONIKANYA - Baharuddin Baharuddin (Pusat Survei Geologi, 2007)
Volcanic rocks which crop out at Long Bia area, east Kalimantan, consist of basaltic andesite to rhyolite in composition. They are in the form of lava, dykes, and pyroclastics. Stratigraphically, the rocks belong the Tertiary Quaternary Metulang Volcanics. Petrographically, the rocks have porphyritic texture with plagioclase, feldspar, and pyroxene phenocrysts that are embedded within a groundmass. Geochemical characteristic of major elements compose of SiO2 (52,8 - 62,5 wt.%), TiO2 (0,57- 0,75wt.%), Al2O2 (15.4- 8,6 wt.%), CaO (5,4-9,4 wt. %) dan MgO (3,21-7,89 wt.%) with depletion on trace elements (Nb, Zr, and Y). In contrast, light rare earth elements (La, Ce, and Nd) and large ion lithophile elements (Ba, Rb. K, and Sr) exhibit enrichment. Characteristics of petrology and geochemistry of the Metulang Long Bia Volcanics indicate that they were formed In an island arc environment and it is interpreted to be related to the Borneo-Palawan subduction activity during the Tertiary-Quaternary time. Keywords : Petrology, geochemistry, Metulang Long Bia, tectonics